2021
DOI: 10.1186/s12866-021-02085-6
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping of sub-Saharan Africa Salmonella strains isolated from poultry feces using multiplex PCR and whole genome sequencing

Abstract: Background Salmonella enterica remains a leading cause of food-borne diseases worldwide. Serotype information is important in food safety and public health activities to reduce the burden of salmonellosis. In the current study, two methods were used to determine serotypes of 111 strains of Salmonella isolated from poultry feces in Burkina Faso. First, Salmonella Multiplex Assay for Rapid Typing (SMART) Polymerase Chain Reaction (PCR) was used to determine the serovars of the S. enterica isolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…This ubiquitous serotype has been closely linked to poultry since 1937 and is now spread in several African countries [ 43 ]. In the current decade in West Africa, the finding of the expansion of Salmonella Kentucky in the poultry sector has also been reported by Igomu et al [ 44 ] and Kagambèga et al [ 45 ].…”
Section: Discussionsupporting
confidence: 61%
“…This ubiquitous serotype has been closely linked to poultry since 1937 and is now spread in several African countries [ 43 ]. In the current decade in West Africa, the finding of the expansion of Salmonella Kentucky in the poultry sector has also been reported by Igomu et al [ 44 ] and Kagambèga et al [ 45 ].…”
Section: Discussionsupporting
confidence: 61%
“…The present study concurs with previous research that the T57S substitution detected in par C is not always associated with a quinolone resistance phenotype since it has been found in both resistant and susceptible isolates [ 11 , 29 ]. Feng et al [ 30 ] also found similar results in a study of a Salmonella Goldcoast lineage in Northern Taiwan, where a single T57S mutation was not always sufficient to confer clinically significant resistance.…”
Section: Discussionsupporting
confidence: 93%
“…DNA extraction, library preparation, whole-genome sequencing, assembly, and annotation for the 102 Salmonella strains were completed as previously reported [ 11 ]. Briefly, libraries were prepared using Nextera XT DNA library preparation kits, which were sequenced using either a 300 or 500 cycle Illumina MiSeq version 2 reagent kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we studied only one Salmonella colony per sample, we were not able to identify cases of sandwich contamination with several different serotypes in this study. Twelve of these 16 serotypes have already been detected in food animals or edible vegetables in Burkina Faso, between 2008 and 2018: Agona (cattle, poultry, fish), Brancaster (cattle, poultry), Bredeney (cattle, poultry, fish, lettuce), Derby (poultry, fish, sheep), Enteritidis (poultry), Hato (cattle, poultry), Kaapstad (poultry, pigs), Kentucky (poultry, fish), Muenster (cattle, poultry, pigs, fish, hedgehogs), Poona (cattle, poultry, fish), Tennessee (cattle), and Tilene (cattle, poultry, fish) [2][3][4][31][32][33]. Eight of these 16 serotypes were also reported in humans in this country (Bredeney, Derby, Enteritidis, Kentucky, Muenster, Poona, Tilene, and Tennessee) [34][35][36].…”
Section: Plos Onementioning
confidence: 99%